2020
DOI: 10.1126/sciadv.aaz4796
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in ACTL7A causes acrosomal ultrastructural defects in human and mouse sperm as a novel male factor inducing early embryonic arrest

Abstract: Early embryonic arrest is a challenge for in vitro fertilization (IVF). No genetic factors were previously revealed in the sperm-derived arrest of embryonic development. Here, we reported two infertile brothers presenting normal in conventional semen analysis, but both couples had no embryos for transfer after several IVF and intracytoplasmic sperm injection (ICSI). Whole-exome sequencing identified a homozygous missense mutation of ACTL7A in both brothers. This mutation is deleterious and causes sperm acrosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 29 publications
7
70
0
Order By: Relevance
“…[14][15][16][17][18][19] Recently, ACTL7A was added as another male factor associated with TFF due to reduced expression and abnormal localization of PLCz. 23 In the present study, we investigated 21 male individuals who underwent at least one ICSI cycle without successful fertilization and identified three homozygous pathogenic variants in ACTL9 impacting the ultrastructure of the PT, ultimately leading to absent or abnormal localization of PLCz with subsequent oocyte activation failure and TFF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19] Recently, ACTL7A was added as another male factor associated with TFF due to reduced expression and abnormal localization of PLCz. 23 In the present study, we investigated 21 male individuals who underwent at least one ICSI cycle without successful fertilization and identified three homozygous pathogenic variants in ACTL9 impacting the ultrastructure of the PT, ultimately leading to absent or abnormal localization of PLCz with subsequent oocyte activation failure and TFF.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Most recently, it was reported that pathogenic variants in ACTL7A (MIM: 604303) led to reduced expression and abnormal localization of PLCz, thereby identifying this genetic variant as a potential cause of TFF. 23 In the present study, we used whole-exome sequencing (WES) and identified three homozygous variants in ACTL9 (actin like 9 [HGNC: 28494, GenBank: NM_178525.5]) in males from 21 couples suffering from TFF or poor fertilization. Our results suggest that mutant ACTL9 has weakened or lost interaction with ACTL7A that causes abnormal localization of PLCz and a loosened PT structure, ultimately leading to failure of oocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…The semen analysis was based on the standard of the fifth edition of the WHO guidelines. A normal semen sample should be equipped with at least a concentration of 15 × 10 6 /ml, a total motility of 40%, and a normal morphology rate of 4% ( Xin et al, 2020 ). Standard density-gradient centrifugation was performed for sperm selection as previously described ( Huang et al, 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…Loos-of-function cause spermatogenic or early embryonic arrest/failure. Recently, was observed a reduced expression and abnormal localization of phospholipase C zeta (PLCζ) in both ACTL7A/Actl7a-mutated men and mice [ 25 , 47 , 50 ].…”
Section: Crispr/cas9 and Infertilitymentioning
confidence: 99%